A Record of Critically Endangered Assam Roofed Turtle Pangshura sylhetensis from Pani-Dihing Bird Sanctuary, Assam, India - Choudhury, Anwaruddin (Journal of the Bombay Natural History Society (JBNHS), 2024)
No Abstract.